Changes in corneal endothelial cell loss in different regions in patients with cataracts and peripheral anterior synechiae after phacoemulsification combined with goniosynechialysis - Huang, Dan; Zhu, Tingting; Luo, Xiangying; Xi, Ting; Liu, Zhenxing (Frontiers in Medicine, 2025)
PureposeTo evaluated regional changes in regional corneal endothelial cell density and morphology during the first month after phacoemulsification with intraocular lens implantation combined with goniosynechialysis (PEI+GSL) in cataract eyes with peripheral anterior synechiae (PAS).MethodsIn this single-center retrospective study, 30 patients with cataract and PAS who underwent PEI+GSL were evaluated preoperatively and 1 month postoperatively. Corneal specular microscopy (EM-4000, Tomey, Japan) was used to examine and compare the corneal endothelial cells (CECs) across seven corneal regions—central, superior, nasal-superior, nasal-inferior, inferior, temporal-inferior, and temporal-superior from preoperative and 1 month postoperative. This study analyzed the variations in corneal endothelial cell density (CD), average size (AVG), coefficient of variation (CV), and hexagonality coefficient (6A) across these regions.ResultsPEI+GSL led to a reduction in corneal endothelial CD in all regions. No significant difference in endothelial cell loss was observed between the central and any individual peripheral region. However, significant differences were detected among the peripheral regions themselves. The CV also showed statistical disparities between the central and peripheral regions. No statistically significant differences were found in the AVG and 6A of corneal endothelial cells across different regions. Postoperatively, both the central and peripheral corneal endothelial CD decreased, AVG increased, 6A decreased, and CV increased.ConclusionThese findings suggest that PEI+GSL in patients with cataracts and PAS predominantly affects corneal endothelial CD and CV in the peripheral region, indicating that the surgery induces regional morphological alterations in peripheral corneal endothelial cells.